The Influence of Fe Substitution in Lanthanum Calcium Cobalt Oxide on the Oxygen Evolution Reaction in Alkaline Media. Issue 9 (1st January 2016) - Abreu-Sepulveda, Maria A.; Dhital, Chetan; Huq, Ashfia; Li, Ling; Bridges, Craig A.; Paranthaman, M. Parans; Narayanan, S. R; Quesnel, David J.; Tryk, Donald A.; Manivannan, A.
Abstract : The effect due to systematic substitution of cobalt by iron in La0.6 Ca0.4 CoO3 perovskites on the oxygen evolution reaction (OER) in alkaline media has been investigated. These compounds were synthesized by a facile glycine-nitrate synthesis and the phase formation was confirmed by X-ray and neutron powder diffraction analysis. The apparent OER activity was evaluated by quasi-steady state current measurements in alkaline media using a traditional three-electrode system. X-ray photoelectron spectroscopy shows an increase in Fe substitution causes an increase in the surface concentration of various Co oxidation states. A Tafel slope in the vicinity of 60 mV/decade and electrochemical reaction order for OH − near unity were found for the unsubstituted compounds. A decrease in the Tafel slope to 49 mV/decade was observed when iron is incorporated in high amounts in the perovskite structure. The area specific current density showed dependence on the Fe fraction; however, the dependence of specific current density with Fe fraction is not linear. We believe that the iron incorporation in the La0.6 Ca0.4 CoO3 perovskites decreases the electron transfer barrier and facilitates the formation of cobalt-hydroxides.